The problems of using electronic document flow during telework - Bahorina, Snezhana E. (Journal of the Belarusian State University. Law, 2019)
This article presents methods of the conclusion of employment agreement on telework. Particular attention is paid to the usage of an electronic document as well as its probable alternatives in this case. The author proposes to amend the Law of the Republic of Belarus «About electronic document and electronically arranged signature» and to recognize the validity of other types of electronic document on the basis of the research results. The importance of their legal application is related to the specifics of the employment agreement on telework and its expansion. However, the real possibility of usage of other types of electronically arranged signature will appear in case of developed mechanism for online verification of the authenticity and integrity of the employment agreement.
Keywords: telework; employment contract; electronic document; document in electronic format; electronically arranged signature; conclusion of employment agreement